MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY PADA MATERI GEOMETRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Putu Dian Eka Wariningsih; I Made Citra Wibawa; Gede Wira Bayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning three-dimensional geometry in elementary schools still faces low conceptual understanding due to limited visualization and the dominance of two-dimensional media, which affects students’ learning outcomes. This study aims to analyze and examine the validity and effectiveness of AR-based interactive learning media. The research employed a R&D approach using the ADDIE model. The subjects included 28 fifth-grade students, one teacher, and two media experts and two subject-matter experts. Data were collected through validation questionnaires, teacher and student responses, and pre-test and post-test instruments, and analyzed descriptively and inferentially. The results show that the AR media achieved very high validity (media experts 4.9; material experts 4.8), very good practicality (teacher response 97.71% and student response 94.55%), and effectiveness in improving learning outcomes with p<0.05. In conclusion, AR-based learning media is effective in improving students’ geometry learning outcomes. The implication, AR media has strong potential as an interactive and meaningful mathematics learning.